La Cartera de Crédito y su Incidencia en la Rentabilidad de la COAC Sol de los Andes Matriz Riobamba, periodo 2020-2021. - Lema Illicachi, Manuel Fernando (2023)
The following investigation is titled "The credit portfolio and its impact on the profitability of the Savings and Credit Cooperative "Sol de los Andes" Riobamba, during the period 2020-2021". The objective was to evaluate the credit portfolio and its incidence on profitability, it is important to say that the aforementioned was approached as field research, since the company was contacted, documentary because several copies were reviewed that denote relevant information and to be able to obtain results, is non-experimental, with a qualitative approach and a descriptive level since each of the characteristics of the variables presented and it is concluded by stating that the credit portfolio of the COAC "Sol de los Andes" affects profitability, because despite the decrease in the delinquency rate and when comparing the years under study, a slight recovery is noted that when carrying out the analysis of economic profitability, financial and on its income it is represented at 0 since in the year 2021 without good it is true, presents a gross profit of 200.00 and a net profit of 127.50 and when applying the formula corresponding to profitability they are not proportional. For this reason, we find different chapters where they will be of great importance for the understanding of it: CHAPTER I: We describe the problem, the objectives, hypotheses and questioning that guided this research project. CHAPTER II: Theoretical framework, background and preliminary knowledge of the COAC "SOL DE LOS ANDES" CHAPTER III: Methodology, that with the correct application allowed that the objectives were achieved. CHAPTER IV: Results, that show if the credit portfolio has an impact on profitability. CHAPTER V: Conclusions and recommendations.